VEGFR Inhibitors for Uterine Metastatic Perivascular Epithelioid Tumors (PEComa) Resistant to mTOR Inhibitors. A Case Report and Review of Literature - Liapi, Aikaterini; Mathevet, Patrice; Herrera, Fernanda G.; Hastir, Delfyne; Sarivalasis, Apostolos (Frontiers in Oncology, 2021)
Uterine perivascular epithelioid cell tumors (PEComas) are rare neoplasms. PI3K/AKT/mTOR pathway upregulation is critical for their pathogenesis and is often associated with TSC1/TSC2 inactivation. Although first line mTOR inhibitors are an effective treatment, metastatic PEComas eventually progress. A 53-year-old woman presented a four-month history of post-menopausal vaginal bleeding. Clinical and radiological examination detected a uterine mass and a single S1 bone lesion. The patient underwent a radical hysterectomy and bone biopsy. The anatomopathological evaluation concluded to an oligo-metastatic uterine PEComa. The tumor harbored a heterozygous deletion of 9q34 that contains the TSC1 gene. Concerning the primary lesion, the resection was complete and the single bone metastasis was treated with radiotherapy. Three months later, the patient presented bone, lung and subcutaneous metastatic progression. An everolimus and denosumab treatment was initiated. After two years of treatment, a clinically significant bone, lung and subcutaneous progression was detected. Following a literature review of the possible therapeutic options, we initiated a second line treatment by pazopanib. This treatment resulted in regression of the subcutaneous lesions and stability of lung and bone metastases. In this challenging, rare setting, our report suggests single agent, anti-angiogenic, tyrosine kinase inhibitor to be effective as second line treatment of metastatic uterine PEComa progressing on mTOR inhibitors.